Intersex in the clam Scrobicularia plana (Da Costa): Widespread occurrence in English Channel estuaries and surrounding areas. Issue 2 (30th June 2015) - Pope, N.D.; Childs, K.; Dang, C.; Davey, M.S.; O'Hara, S.C.M.; Langston, K.; Minier, C.; Pascoe, P.L.; Shortridge, E.; Langston, W.J.
Highlights: We report the incidence of intersex (ovotestis) in Scrobicularia plana from the Channel region. Overall, 58% of populations from 108 locations contained intersexed clams. Incidence and severity of intersex were not related to size or parasitism of individuals. Intersex in S. plana is a useful tool to assess endocrine disruption in estuaries. Abstract: Estuarine clams Scrobicularia plana were sampled from 108 intertidal locations around the English Channel and adjacent areas. Although S. plana is believed to be a strict gonochorist, 58% of the populations sampled included intersexed individuals (described as male clams exhibiting ovotestis). Over the entire region, on average, 8.6% of male clams exhibited intersex, although proportions of affected males ranged from 0% to 53% depending on location. The severity of intersex was assessed using a simple classification scale, with the majority of individuals showing low levels of impact. Sex ratios were significantly skewed at some sites. There were no significant relationships between incidence or severity of intersex; or with size or parasitism of individual clams. Intersex in S. plana is a useful tool to assess endocrine disruptive effects in estuaries, although mechanisms of impact and causative agents remain uncertain.